Copyright Infringement of Films Through Internet Means From a Legal Perspective - Antono, Antono; Hutapea, Haposan Seventino Octavianus (Universitas Syiah Kuala, 2025)
Copyright infringement on the internet is not something new. Along with the development and ease of accessing the internet, it has negative impacts such as the increasing number of copyright infringement cases. This article explains that the government and ministers have the authority to prevent information technology-based copyright infringement, namely supervision, coordination and closing user content that violates copyright on the internet. Copyright infringement on the internet can even be said to be more than copyright infringement that is not via the internet. Copyright is not limited by its media so that if it is transformed, for example books, films, songs and others, which are shared on the internet then the copyright lies with the owner of the original form. The act of using the economic rights of the creator without the permission of the creator is said to be an act without permission or an unofficial act, in criminal acts it is said to be a copyright crime.